Community and household shocks and coping strategies: Findings from the ninth round of the Myanmar Household Welfare Survey (April - October 2025) - van Asselt, Joanna; Aung, Zin Wai (International Food Policy Research Institute, 2026)
The ninth round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, was conducted between July and October 2025. This round follows eight previous rounds carried out since December 2021 and reflects conditions during April – October 2025. This report presents updated evidence on the conflict, climatic, service, and economic shocks households face and the coping strategies they adopt.